PENGEMBANGAN RESTFUL API UNTUK MEMBANTU PEMBUDIDAYA IKAN LELE DALAM SISTEM MANAJEMEN RANTAI PASOK “PANEN-PANEN” - Yunhasnawa, Yoppy; Aprilianto, Salies; Allam, Muhammad Faiq; Himawan, Dhimas Arbi Sukma (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Food is a necessity that cannot be eliminated in life in this world. Food is one of the benchmarks for a country whether the country is prosperous or not in meeting the food needs of its citizens. The category of food that Indonesian people really like is catfish. The high market demand for catfish has resulted in catfish cultivators being overwhelmed in meeting these food needs. One effort that can be done is to initiate the design of a